2009
DOI: 10.1016/j.bbrc.2009.01.032
|View full text |Cite
|
Sign up to set email alerts
|

p21 functions in a post-mitotic block checkpoint in the apoptotic response to vinblastine

Abstract: We have shown previously that in KB-3 (HeLa) cells vinblastine causes downregulation of the CDK inhibitor p21 through a c-Jun regulated pathway. To test the hypothesis that p21 downregulation is necessary to alleviate a protective function, we transfected p21 in KB-3 cells and examined the apoptotic response to vinblastine. The results showed that cells overexpressing p21 were apoptosisresistant, not through an ability of p21 to cause cell cycle arrest prior to mitotic arrest, but through altering the fate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…p21 is recognized to play a role in the protection of cancer cells from stress and DNA damage [ 25 ]. Our findings indicated that p21 was also a direct target of miR-106b.…”
Section: Resultsmentioning
confidence: 99%
“…p21 is recognized to play a role in the protection of cancer cells from stress and DNA damage [ 25 ]. Our findings indicated that p21 was also a direct target of miR-106b.…”
Section: Resultsmentioning
confidence: 99%
“…However, p21 has also been linked to maintenance of self-renewal capacity in leukemic and normal hematopoietic stem cells, indicating that cellular context can impact on functional properties of these regulators (Cheng et al, 2000;Viale et al, 2009). Although, to our knowledge, there are no reports on a role for p21 in CC-IC self-renewal, p21 has a well-established role in protecting colon cancer cells against a variety of stress stimuli, including exposure to radiation and chemotherapy (Mahyar-Roemer and Roemer, 2001;Bene and Chambers, 2009;Gorospe et al, 1996;Sharma et al, 2005;Tian et al, 2000). These studies point to the plausibility that therapy resistance may be linked to tumor initiation and maintenance mechanisms and that pathways driving self-renewal may also function to protect CC-ICs when exposed to environmental stress.…”
Section: Significancementioning
confidence: 99%
“…Mechanisms of apoptosis and their effector proteins included pro-apoptotic protein, anti-apoptotic Bcl-2 family members, and inhibitor of apoptosis proteins (IAP) [26]. BIM, Caspase3, HSP60, p21 and p53 were all pro-apoptotic proteins, which may contribute to apoptosis induction [27][28][29][30]. Caspase3 functions as an executor of apoptosis by activating DNA fragmentation [31].…”
Section: Discussionmentioning
confidence: 99%